Association between the COMT gene val158met polymorphism and borderline personality disorder: A meta-analysis. (December 2017) - Liu, Jianbo; Nie, Guanghui; Guo, Wenqin; Gong, Jingbo; Xiao, Bo; Cui, Xilong; He, Yuqiong; Meng, Tiantian; Shen, Yanmei; Wu, Junduan
Highlights: This is the first meta-analysis of the association between the COMT Val158Met mutation and BPD. This study further explained the association between the COMT gene rs4680 and BPD by increasing sample size. The populations included in this meta-analysis were mainly composed of Caucasians. The COMT Val158Met mutation may not play a role in BPD development.